Sosialisasi dan Lokakarya Akreditasi Badan Akreditasi Nasional (BAN) PAUD dan PNF di Kecamatan Penajam Kabupaten Paser Utara Kalimantan Timur - Heppy Liana; Kartika Fajriani; Yeni Aslina; Hasbi Sjamsir (TAAWUN, 2023)
Currently, the government continues to encourage PAUD institutions to apply for accreditation. Several institutions in Penajam District, North Paser Regency, and East Kalimantan have not submitted on the grounds that (1) Teachers are still unfamiliar with the use of technology related to uploading documents in the system, (2) Teachers experience confusion related to providing the types of documents for each accreditation item, (3) Teacher incomprehension of the document format for each accreditation item. This community service activity was carried out in collaboration with the East Kalimantan Nahdlatul Ulama University together with the National Accreditation Board for PAUD and PNF Kaltim located in North Penajam Paser Regency and the participants consisted of supervisors and supervisors as well as heads of PAUD and PNF units who in their implementation combined theory and practice of filling out the SISPENA application. The aim is to help achieve the level of achievement of the quota for PAUD and PNF units that will participate in accreditation. The result was a common perception about accreditation, understanding of accreditation documents, and PAUD units were ready to upload documents to SISPENA